GIS and Spatial Analysis: Introductory Chapter - Viana, Cláudia (2023)
Geographic Information Systems (GIS) and spatial analysis are considered to be a science in their own right, with a solid theoretical and methodological basis. The science behind GIS and spatial analysis has been coined as geoinformatics, which is defined as the application of Geographic Information Science (GISc) to solve problems in earth and environmental sciences. Geoinformatics involves the collection, storage, processing, analysis, visualization, and dissemination of geographic information. Spatial analysis is a fundamental aspect of geoinformatics and is used to study the distribution and relationship between geographic objects and events. Spatial analysis involves the use of statistical, mathematical, and computational techniques to explore patterns and trends in geographic data. It also allows users to create spatial models and make predictions based on different scenarios. The science behind spatial analysis involves the application of mathematical, statistical, and computational methods to analyze and interpret spatial patterns and relationships between geographic objects and events. It draws on a variety of disciplines such as geography, mathematics, statistics, computer science, and remote sensing to provide a comprehensive understanding of spatial data. The theoretical basis of spatial analysis includes concepts such as spatial autocorrelation, spatial heterogeneity, and spatial dependence, which helps to explain the spatial patterns and relationships observed in geographic data. Spatial analysis methods can be broadly categorized into descriptive, exploratory, and inferential techniques, which are used to visualize, explore, and test spatial data. Some common spatial analysis techniques include spatial interpolation, spatial regression, spatial clustering, spatial smoothing, and spatial econometrics. These methods can be applied to a wide range of spatial data, including point data, areal data, and network data. Spatial analysis has become increasingly important in many fields such as public health, environmental studies, urban planning, and criminology, among others. It provides a powerful tool to study spatial problems and make informed decisions based on spatial data. Advances in technology have also led to the development of new spatial analysis methods, such as machine learning and deep learning, which are being applied to address complex spatial problems.